Efektywność gospodarstw rolnych indywidualnych - Urban, Stanisław (The Effectiveness of Individual Farms, 2005)
As far as the farm effectiveness is concerned we can distinguish the productive effectiveness, economical and social ones. The first - the productive effectiveness characterizes the output of a farm per unit. The second - economical - is estimated by determining the output of production per 1 ha arable land and the relation of the costs production to proceeds. The last one, but not the least, the social effectiveness indicates in which level farmers and their family's lives are, including the quality of nourishment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 437-446